Determination of Risk Factors for Severe Life-Threatening Course of Multisystem Inflammatory Syndrome Associated with COVID-19 in Children - Ilia S. Avrusin; Natalia N. Abramova; Konstantin E. Belozerov; Gleb V. Kondratiev; Liudmila V. Bregel; Olesya S. Efremova; Alla A. Vilnits; Julia E. Konstantinova; Eugenia A. Isupova; Tatiana L. Kornishina; Vera V. Masalova; Eugeniy Yu. Felker; et al. (MDPI AG, 2023)
Multisystem inflammatory syndrome associated with COVID-19 in children (MIS-C) is a life-threatening condition that often requires intensive care unit (ICU) admission. The aim of this study was to determine risk factors for severe/life-threatening course of MIS-C. The study included 166 patients (99 boys, 67 girls) aged 4 months-17 years (median 8.2 years). The criterion of severity was the fact of ICU admission. To conduct a comparative analysis, MIS-C patients were divided into two groups: patients hospitalized in the ICU (n = 84, 50.6%) and those who did not need ICU admission (n = 82, 49.4%). Patients with a more severe course of MIS-C were significantly older. They had a higher frequency of signs such as rash, swelling, hepatomegaly, splenomegaly, and neurological and respiratory symptoms. Hypotension/shock and myocardial involvement were much more common in patients with severe MIS-C. These patients had a more significant increase in CRP, creatinine, troponin, and D-dimer levels. Additionally, the presence of macrophage activation syndrome was higher in patients admitted to the ICU. Conclusion: Nineteen predictors of severe course of MIS-C were found, out of which hepatomegaly, splenomegaly, D-dimer > 2568 ng/mL, troponin > 10 pg/mL were mainly associated with the probability of being classified as early predictors of severe MIS-C requiring ICU admission.